Structure and Magnetic Properties of SrFe12O19/CoFe2O4 Nanocomposite Ferrite - Nga, Trần Thị Việt; Thi Lan, Nguyen; Thanh Loan, To; Ha, Hoang (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: Nanocomposite particles SrFe 12 O 19 / CoFe 2 O 4 were synthesized by sol-gel method. The nanocomposites are formed at the calcining temperature around 850 o C in 5 hours. The phase composition, surface morphology and magnetic properties of the nanocomposites were investigated using XRD, SEM and VSM, respectively. The results show that the magnetic properties of nanocomposite particles are strongly influenced by the molar ratios of the hard and soft phases and particle size distributions. The samples with the mass ratio of R m = SrFe 12 O 19 / NiFe 2 O 4 = 1/3 and 1/5 are characterized with a “bee waist” type hysteresis loop. While all the samples R V show an excellent smooth hysteresis loop and a single – phase magnetization behavior. The coercivity decreases significantly and the magnetization drastically increases with decreasing of volume ratio R V . Keywords : nanocomposite, sol- gel method, exchange coupling.  References [1] D.A. Allwood, G. Xiong, M.D. Cooke, C.C. Faulkner, D. Atkinson, N. Vernier, R.P. Cowburn, Submicrometer Ferromagnetic NOT Gate and Shift Register, Science. 296 (2002) 2003–2006. [2] F.X. Redl, K.S. Cho, C.B. Murray, S. O’Brien, Three-dimensional binary superlattices of magnetic nanocrystals and semiconductor quantum dots, Nature. 423 (2003) 968–971. [3] Z.L. Wang, X.J. Liu, M.F. Lv, P. Chai, Y. Liu, X.F. Zhou, J. Meng, Preparation of One-Dimensional CoFe2O4 Nanostructures and Their Magnetic Properties, J. Phys. Chem. C. 112 (2008) 15171–15175. [4] S.O. Hwang, C.H. Kim, Y. Myung, S. Park, J. Park, J. Kim, C. Han, Synthesis of Vertically Aligned Manganese-Doped Fe3O4 Nanowire Arrays and Their Excellent Room-Temperature Gas Sensing Ability, J. Phys. Chem. C. 112 (2008) 13911–13916. [5] M. A. Moskalenko, V.M. Uzdin, H. Zabel, Manipulation by exchange coupling in layered magnetic structures, J. Appl. Phys. 115 (2014) 053913. [6] Gu FM, Pan WW, Liu QF, Wang JB. Electrospun magnetic SrFe12O19 nanofibres with improved hard magnetism, J. Phys. D-Appl. Phys. 46 (2013) 445003– 10. [7] Rakshit R, Mandal M, Pal M, Mandal K. Tuning of magnetic properties of CoFe2O4 nanoparticles through charge transfer effect , Appl. Phys. Lett. 104 (2014) 092412– 0912417. [8] A.L. Xia, C.H. Zuo, L. Chen, C.G. Jin, Y.H. Lv, Hexagonal SrFe12O19 ferrites: Hydrothermal synthesis and their sintering properties, J. Magn. Magn. Mater. 332 (2013) 186-191. [9] A.L. Xia, X.Z. Hu, D.K. Li, L. Chen, C.G. Jin, C.H. Zuo, S.B. Su, Facile hydrothermal synthesis of core/shell-like composite SrFe12O19/(Ni,Zn)Fe2O4 nanopowders and their magnetic properties, Electron. Mater. Lett. 10 (2014) 423-426. [10] B.N. Pianciola, E. Lima Jr., H.E. Troiani, L.C.C.M. Nagamine, R. Cohen, R.D. Zysler, Size and surface effects in the magnetic order of CoFe2O4 nanoparticles , J. Magn. Magn. Mater. 377 (2015) 44-51. [11] C.N. Chinnasamy, B. Jeyadevan, K. Shinoda, K. Tohji, D.J. Djayaprawira, M. Takahashi, R.J. Joseyphus, A. Narayanasamy, Unusually high coercivity and critical single-domain size of nearly monodispersed CoFe2O4 nanoparticles, Appl. Phys. Lett. 83 (2003) 2862-2864. [12] Haibo Yang, Miao Liu, Ying Lin, Guoqiang Dong, Lingyan Hu, Ying Zhang, Jingyi Tan, Enhanced remanenc e and (BH) max of BaFe12O19 /CoFe2O4 composite ceramics prepared by the microwave sintering method, Materials Chemistry and Physics. 160 (2015) 5-10. [13] Juan Dong, Yi Zhang, Xinlei Zhang, Qingfang Liu, Jianbo Wang, Improved magnetic properties of SrFe12O19/FeCo core–shell nanofibers by hard/soft magnetic exchange–coupling effect, Materials Letters. 120 (2014) 9-12. [14] Wei Zhong, Weiping Ding, Ning Zhang, Jianming Hong, Qijie Yan, Youwei Du , Key step in synthesis of ultrafine BaFe12O19 by sol-gel technique, J. Magn. Magn. Mater. 168 (1997) 196-202. [15] K. W. Moon, S. G. Cho, Y. H. Choa, K. H. Kim, and J. Kim, Synthesis and magnetic properties of nano Ba-hexaferrite/NiZn ferrite composites, phys. stat. sol. (a) 204 (12) (2007) 4141 – 4144. [16] Y.H. Liu, S.G.E.T. Velthuis, J.S. Jiang, Y. Choi, S.D. Bader, A.A. Parizzi, H. Ambaye, V. Lauter, Magnetic structure in Fe/Sm-Co exchange spring bilayers with intermixed interfaces, Phys. Rev. B. 83 (2011) 174418. [17] Ailin Xia, Suzhen Ren, Junshu Lin, Yue Ma, Chen Xu, Jinlin Li, Chuangui Jin, Xianguo Liu, Magnetic properties of sintered SrFe12O19-CoFe2O4 nanocomposites with exchange coupling, J. Alloys Compd. 653 (2015) 108- 116. [18] C.B. Rong, H.W. Zhang, R.J. Chen, S.L. He, B.G. Shen, The role of dipolar interaction in nanocomposite permanent magnets, J. Magn. Magn. Mater. 302 (2006) 126. [19] K.P. Remya, D. Prabhu, S. Amirthapandian, C. Viswanathan, N. Ponpandian, Exchange spring magnetic behavior in BaFe12O19 /Fe3O4 Nanocomposites, J. Magn. Magn. Mater. 406 (2016) 233 – 238. [20] Rui Xiong, Weiwei Li, Chunlong Fei, Yong Liu, Jing Shi, Exchange-spring behavior in BaFe12O19 -Ni0.5Zn0.5Fe2O4 nanocomposites synthesized by a combustion method, Ceramics International. 42 (2016) 11913-11917.